A qualitative evaluation of online active learning modalities in the chronic wound management lecture of nursing students′ experiences in Turkey. Issue 4 (November 2022) - Sengul, Tuba; Shoqirat, Noordeen; Singh, Charleen; Mahasneh, Deema; Karadag, Ayise
Highlights: For the first time in Turkey, the chronic wound care track program was integrated into nursing education. In the chronic wound management lecture, active learning modalities provided the student with a better understanding of the theoretical knowledge and difficult case solutions related to the care of chronic wounds with all its concepts. The chronic wound management lecture designed with video and various games can facilitate learning the management of various and complex wounds that students encounter for the first time during the course, without feeling stress and anxiety. This study will pave the way for serious inclusion in nursing education so that it can be effective in improving the quality and outcomes of chronic wound care in the future.